Advances on broad-band wireless computing, communication and applications : proceedings of the 12th International Conference on Broad-Band Wireless Computing, Communication and Applications (BWCCA-2017) /: proceedings of the 12th International Conference on Broad-Band Wireless Computing, Communication and Applications (BWCCA-2017). (2018) - Unknown
No abstract available